Necrobiosis lipoidica in diabetic patients: pathogenetic and clinical features - Daria Alexandrovna Semenova; Alla Yur'evna Tokmakova (Сахарный диабет)
Necrobiosis lipoidica (NL) is a chronic skin disease (dermatosis) associated with various metabolic disorders including carbohydrate metabolism.In the last years, NL has been increasingly frequently diagnosed by practitioners probably due to the rise in type 2 diabetes mellitus morbidity in thegeneral population. Moreover, association of NL with autoimmune thyroid diseases, Crohns disease, ulcerative colitis, sarcoidosis, and vitiligo hasbeen documented. Such cases may be attributed to phenotypic and functional defects of cellular immunity.